A quantitative method to identify microRNAs targeting a messenger RNA using a 3′UTR RNA affinity technique - Shi, Miao (2013)
The identification of specific microRNAs (miRNAs) that target a given messenger RNA (mRNA) is essential for studies in gene regulation, but the available bioinformatic software programs are often unreliable. We have developed a unique experimental miRNA affinity assay whereby a 3′UTR RNA is end-labeled with biotin, immobilized, and then used as a bait sequence for affinity pull-down of miRNAs. After washes and release, cloning and sequencing identify the miRNAs. Binding affinity is quantitated by quantitatvie polymerase chain reaction (qPCR), comparing released and original input concentrations. As an initial demonstration, the TCF8/ZEB1 mRNA affinity pull-down yielded miR-200 family member miRs in the majority of clones, and binding affinity was approximately 100%; virtually all copies of miR-200c bound the immobilized mRNA transcript. For validation in cells, miR-200c strongly inhibited expression of a TCF8 luciferase reporter, native TCF8 mRNA, and protein levels, which contrasted with other recovered miRNAs with lower binding affinities. For Smad4 mRNA, miR-150 (and others) displayed a binding affinity of 39% (or less) yet did not inhibit a Smad4 reporter, native Smad4 mRNA, or protein levels. These results were not predicted by available software. This work demonstrates this miRNA binding affinity assay to be a novel yet facile experimental means of identification of miRNAs targeting a given mRNA.